Perancangan Infrastruktur Jaringan Komputer dalam Mendukung Pembelajaran dan Standar Prasarana Fasilitas Internet di SDN 138 Geger Kalong Girang - Gunarso Gunarso; M. Nursalman; Enjang Ali Nurdin; M. Munir; Muhammad Syafri Syamsudin (Departement of Mathematics Education, 2023)
This research started with the need the implementation of Computer-Based National Assessment (ANBK) at SD Negeri 138 Geger Kalong Girang with the condition that computer and internet network infrastructure was not available, but the implementation of ANBK had to be carried out independently. The purpose of designing this computer network infrastructure is in addition to implementing ANBK well as supporting the learning process for teachers and students for the availability of adequate internet access which can be used for learning purposes. Design of computer network infrastructure to support learning and internet facility infrastructure standards in schools is applied using the PPDIOO concept, namely, Prepare, Plan, Design, Implement, Operate and Optimize. The results of this study indicate that the computer network infrastructure planning is as expected. The ANBK implementation running normally, the results of the bandwidth usage test as a whole running normally and the internet could be accessed very well in the school environment.